The Role of Mediators in Resolving Divorce Cases at The Serang Religious Court Under Supreme Court Regulation No. 1 of 2016 - Aldestianah Putri Abu Bakar; Fathullah Fathullah; Santy Fitnawati WN (CV. Era Digital Nusantara, 2025)
Mediation is one of the mandatory dispute resolution efforts in civil cases, including divorce cases handled by the Religious Court. This mechanism serves as an alternative that allows the parties to reach a peaceful settlement without going through a lengthy, complex, and costly litigation process. Supreme Court Regulation (PERMA) Number 1 of 2016 concerning Mediation Procedures in Court strengthens the mediator’s role as a facilitator of peace and reinforces the obligation of mediation in civil dispute resolution. This study aims to analyze the role of mediators in resolving divorce cases at the Religious Court of Serang based on the provisions of the regulation. The research employs a normative juridical method with a statutory approach, supported by empirical data obtained through interviews with mediators at the Religious Court of Serang. This combination aims to provide a comprehensive understanding of the mediator’s role from both normative and practical perspectives. The results of the study indicate that mediators play an important role in facilitating communication between parties, managing the mediation process, identifying each party’s interests, exploring possible settlement options, and assisting in formulating final and legally binding agreements. However, the success of mediation is greatly influenced by factors such as the parties’ willingness to reconcile, the mediator’s communication skills, and the existence of clear and consistent regulations